The learning curve for intraoperative neuromonitoring of the recurrent laryngeal nerve in thyroid surgery - Wojtczak, Beata (Langenbecks Arch Surg, 2016)
PURPOSE: Intraoperative neuromonitoring (IONM) of the recurrent laryngeal nerve (RLN) is often used in thyroid surgery. However, this procedure is complex and requires a learning period to master the technique. The aim of the study was to evaluate the learning curve for IONM. METHODS: A 3-year period (2012–2014) of working with IONM (NIM3.0, Medtronic) was prospectively analyzed with a special emphasis on comparing the initial implementation phase in 2012 (101 patients, 190 RLNs at risk) with subsequent years of IONM use in 2013 (70 patients, 124 RLNs at risk) and 2014 (65 patients, 120 RLNs at risk). RESULTS: The rate of successful IONM-assisted RLN identification increased gradually over the 3-year study period (92.11 % in 2012 vs. 95.16 % in 2013 vs. 99.16 % in 2014; p = 0.022), with a corresponding decrease in the rate of technical problems (12.87, 4.3, and 4.6 %, respectively; p = 0.039). The rate of RLN injuries tended to decrease over time: 3.68, 1.55, and 0.83 %, respectively (p = 0.220). Between 2012 and 2014, increases in the sensitivity (71.4 vs. 100 %), specificity (98 vs. 99 %), positive predictive value (62.5 vs. 75 %), negative predictive value (98 vs. 100 %), and overall accuracy of IONM (97.4 vs. 99.6 %) were observed (p = 0.049). Increasing experience with IONM resulted in more frequent utilization of total thyroidectomy (92 % in 2012 vs. 100 % in 2013–2014; p = 0.004). CONCLUSIONS: There was a sharp decrease in the number of technical problems involving equipment setup from 2012 to 2014.